Maternal Judgments of Child Numeracy and Reading Ability Predict Gains in Academic Achievement and Interest. Issue 5 (15th May 2021) - Parker, Philip D.; Sanders, Taren; Anders, Jake; Parker, Rhiannon B.; Duineveld, Jasper J.
Abstract : In a representative longitudinal sample of 2, 602 Australian children (52% boys; 2% Indigenous; 13% language other than English background; 22% of Mothers born overseas; and 65% Urban) and their mothers (first surveyed in 2003), this article examined if maternal judgments of numeracy and reading ability varied by child demographics and influenced achievement and interest gains. We linked survey data to administrative data of national standardized tests in Year 3, 5, and 7 and found that maternal judgments followed gender stereotype patterns, favoring girls in reading and boys in numeracy. Maternal judgments were more positive for children from non‐English speaking backgrounds. Maternal judgments predicted gains in children's achievement (consistently) and academic interest (generally) including during the transition to high school.